Phytochemicals screening, cytotoxicity and antioxidant activity of the Origanum majorana growing in Casablanca, Morocco - Hanane Ennaji; Dounia Chahid; Saadia Aitssi; Abdallah Badou; Naima Khlil; Samir Ibenmoussa (Open Journal of Biological Sciences - Peertechz Publications, 2020)
Origanum majorana is a plant from the Lamiaceae family. It is a medicinal plant used in traditional medicine in Morocco to treat various diseases. This work aims to determine the phytochemical composition of Marjoram, as well as to evaluate its cytotoxic effect on the cells of healthy subjects. All parts of the plant (roots, leaves, stems, etc.) were subjected to selective extraction with different solvents of increasing polarity (Diethyl ether, Dichloromethane, Ethanol, Methanol) using the rotary steamer. The yields obtained are respectively 1.34%, 4.57%, 9.98%, and 10%. The phytochemical tests carried out have detected the presence of polyphenols, tannins, flavonoids, terpenoids, sterols, saponins, and reducing sugars. In contrast, the absence of the family of cardiotonic alkaloids, quinones, and heterosides. Origanum majorana L. exhibited concentration-dependent inhibitory effects on 2,2'-diphenylpicrylhydrazyl (DPPH) with IC50 equal 2.308 mg/ml, related to the presence of the same content of polyphenols and flavonoids but with the lowest concentration of tannin content. The cytotoxicity of the hydro-ethanolic extract of Marjoram was evaluated by the MTT colorimetric method. However, the results obtained that the examined extract was devoid of cytotoxic activity, on the other hand, it induced cell proliferation. O. majorana has good potential to prevent diseases caused by the overproduction of free radicals, and that it can be used as natural antioxidant agents and cell proliferation dependant on concentration.